Proceedings of the 5th International Conference on Physical Education, Sport, and Health (ACPES 2019) 2019
DOI: 10.2991/acpes-19.2019.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Macronutrient Compositions and Sensory Characteristics of Jackfruit Nugget Formulations and Commercially Available Chicken Nugget

Abstract: Jackfruit (Artocarpus heterophyllus) is well known as good source of carbohydrates and fibers. Jackfruit has high phenolic content which could prevent the onset of cardiovascular disease. Jackfruit has large size and low shelf-life, so modifications are needed to made it commercially available. On the other hand, the high consumption of junk food such made prevalence of non-communicable diseases became steadily increased. This research tried to develop new formulation of nugget which has lower fat content and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The characteristics of the subjects who were selected as panelists included: (1) healthy, not colorblind, and do not consume alcohol; (2) not smoking an hour before the implementation of the sensory test; (3) have no allergies or abstinence to one or more components of the foodstuffs to be sensory tested; (4) have experience carrying out sensory tests [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the subjects who were selected as panelists included: (1) healthy, not colorblind, and do not consume alcohol; (2) not smoking an hour before the implementation of the sensory test; (3) have no allergies or abstinence to one or more components of the foodstuffs to be sensory tested; (4) have experience carrying out sensory tests [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies by Febrisiantosa et al (2012) stated that it has high fat and cholesterol content, however, it comprises low fi ber. Kurnia et al (2019) reported that 100 g of chicken nuggets has an energy content of 335.54 kcal, which comprises of 20.72 g carbohydrate, 9.30 g protein, and 23.94 g fat. Despite its popularity, several research tried to create healthier nuggets by reducing the high fat content (Brunner, 2016;Petracci et al, 2013).…”
Section: Introductionmentioning
confidence: 99%